P169 Systemic Pythiosis: presumably, the first human case in India. (20th September 2022) - Joe, Geethu; Soman, Rajeev; Chakraborty, Sourabh; Kothawade, Hrishita; Ramchandani, Nandini; Chakrabarti, Arunaloke
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM:   Objectives: This is the first human case of systemic disease due to Pythium insidiosum reported from India. The case highlights difficulty in diagnosis and management. Methods: A 44-year-old male patient had a peri-esophageal and peri-gastric inflammatory lesion which showed inflammation along with sparsely septate hyphae (Fig. 1), and partially responded to voriconazole (VCZ). After 1.5 years, he developed a massive liver lesion (Fig. 2), and hepatic venous thrombosis which was refractory despite restarting therapy with posaconazole (PCZ). As a desperate measure, surgical excision of the large liver lesion was undertaken. Results: Serum BDG was positive and Serum Galactomannan was negative. There was no tidy explanation for the insidious clinical course of the illness over 1.5 years, partial response to VCZ for the esophageal lesion and inadequate response of the subsequent lesion to PCZ. The liver biopsy specimen showed a flat, feathery growth on SDA which was identified at PGI, Chandigarh by ITS as P. insidiosum. P. insidiosum and additionally Rhizopus microsporus were identified by molecular sequencing from the surgical specimen as well. The patient succumbed to carbapenem-resistant Klebsiella bacteremia in the postoperative stage. Conclusion: The case underscores the insidious course of systemic pythiosis, diagnostic, and management challenges.